Pengaruh Revitalisasi Monumen Nasional Sebagai Penunjang Peningkatan Minat Berkunjung - Rizki Nurul Nugraha; Cahya Gilang Ananda Kresna Putra (Peneliti.net, 2023)
Revitalization as a series of efforts to revive the National Monument area in the process is not an easy thing. In carrying out revitalization there are steps that must be considered so that the revitalization process can be successful. This study aims to determine the effect of revitalization on interest in visiting the National Monument. This research was conducted using descriptive data analysis method with a qualitative approach. From the results of the analysis conducted, it shows that revitalization can affect the interest of tourists to visit tourist attractions.